Chromosome-level genome assembly of the ivory shell Babylonia areolata - Yu Zou; Jingqiang Fu; Yuan Liang; Xuan Luo; Minghui Shen; Miaoqin Huang; Yexin Chen; Weiwei You; Caihuan Ke (Scientific Data)
Abstract The ivory shell Babylonia areolata is an economically important marine benthic gastropod known for its rapid growth and high nutritional value. B. areolata is distributed in Southeast Asia and the southeast coastal areas of China. In this study, we constructed a high-quality genome for B. areolata using PacBio, Illumina, and Hi-C sequencing technologies. The genome assembly comprised 35 chromosomal sequences with a total length of 1.65 Gb. The scaffold and contig N50 lengths were 53.17 Mb and 2.64 Mb, respectively, with repeat sequences constituting 64.46% of the genome. Furthermore, 26,130 protein-coding genes and 96.75% of the genome’s BUSCOs were identified. This inaugural report of a B. areolata genome provides crucial foundational information for further investigations into the biology, genomics, and genetic improvement of economic traits of this species.